Photodynamic therapy with PhotoPoint photosensitiser MV6401, indium chloride methyl pyropheophorbide, achieves selective closure of rat corneal neovascularisation and rabbit choriocapillaris. Issue 1 (21st December 2004) - Ciulla, T A; Criswell, M H; Snyder, W J; Small, W
Abstract : Aim: The new photosensitiser PhotoPoint MV6401, indium chloride methyl pyropheophorbide, was assessed as a possible ocular photodynamic therapy agent in a rat model of experimentally induced corneal neovascularisation and in choriocapillaris closure in the rabbit. Optimal drug and light activation parameters were determined. Methods: MV6401 (Miravant Pharmaceuticals, Inc, Santa Barbara, CA, USA) was activated at 664 nm using a DD3-0665 (Miravant Systems Inc) 0.5 W diode laser. Corneal neovascularisation in rats was induced using an N-heptanol technique. The evaluated drug dosages, light dosages, and post-injection activation times ranged from 0.01–0.1 μmol/kg, 5–25 J/cm 2, and 10–60 minutes, respectively. The efficacy of MV6401 on normal choriocapillaris and choroidal vessels was evaluated in rabbits with indirect ophthalmoscopy, fundus photography, fluorescein angiography, and histology. In rabbits, the evaluated drug dosages, light dosages, and post-injection activation times ranged from 0.025–0.25 μmol/kg, 3.3–20 J/cm 2, and 10 minutes, respectively. Results: In the rat corneal neovascularisation model, an optimal intravenous drug dosage of 0.075 μmol/kg was activated by a 20 J/cm 2 light dose at 10 minutes after drug administration, the results of which demonstrated early evidence of efficacy in ocular neovascularisation. In rabbits, closure of the normal choriocapillaris was selectively achieved at a drug dosage of 0.15 μmol/kg using light doses from 3.3 to 20 J/cm 2 . Conclusion: PhotoPoint MV6401 is a potent photosensitiser that demonstrates both efficacy and selectivity in experimental ocular models.